Using Predict-O-Gram Strategy to Improve Student’s Ability in Reading Comprehension - Ratna Nery; Nyayu Yayu Suryani (ELT-Lectura, 2021)
Abstract: The objective of the study was to find out whether or not there was a significant difference in reading comprehension achievement between the students who were taught by using Predict-O-Gram Strategy and that of those who were not. The method used in this study was a quasi-experimental method. The sample of the study was 54 students, which divided into two groups, namely experimental group (class VIII.B) and a control group (class VIII.C), each of them consisted of 27 students. To collect the data the written test was used in the form of multiple-choice. Before giving the test, the test was tried out to non sample students of the eighth grade students of MTs Subulussalam Kayuagung class VIII. A in order to know whether or not the test was valid and reliable for sample not. The data obtained were analyzed by t-test and the calculation was done with SPSS (Statistical Package for Social Science) version 20. Based on the result of independent sample t-test, It found that there was a significant difference in reading comprehension achievement between the students who were taught by using Predict-O-Gram Strategy and that of those who were not. Keywords: predict-o-gram strategy, reading comprehension